IMPLEMENTING RELIGIOUS MODERATION IN THE QUR'AN PERSPECTIVE: A SOLUTION TO EDUCATE THE LIFE OF NATION AND STATE COMMUNITIES IN INDONESIA (International Conference on Social and Islamic Studies, 2021)
The face of Islam in Indonesia, which is predicted to be the largest Muslim in the world, is a very urgent spotlight in playing a moderating role in religion. The essence of Islamic teachings is moderation for its adherents. Moderation in this case is a form of religious understanding that is very much in line with the existence of Islam in Indonesia, which has a lot of natural wealth developed, as well as wealth in a variety of customs, ethnicities and religions. This research aims to provide an integrated solution of the Al-Qur'an regarding the life of the people in the nation and state through religious moderation, which is then expected to be the glue for the dynamics of various Islamic understandings, as well as to provide solutions in the midst of various problems in religion and global civilization. This research method is Library Research. The result is that one solution that can be given is how the mind side understanding of religious moderation will be very appropriate if it is juxtaposed with the practice of tawajun (balanced) or tawasshuth (intermediate) attitudes with the correct understanding through practicing the messages that are streamed in the Qur'an. In conclusion, the word of God reflects on the aspect of moderation. At least the aspect of acknowledging the truth on the other side, upholding the thought of a tolerant attitude, respecting differences of opinion and not imposing a will by means of violence, this is what then becomes a solution to overcome this. What is described above refers to the information contained in Al-Hujarat: 13 (about respecting diversity and the willingness to interact). Hud: 118-119 (concerning religious expression wisely and politely), as well as the principle of convenience in accordance with the abilities of al-Baqarah: 185, and an-Nisa’: 28.